The Influence of Organizational Culture on Motivation to Learn in Vocational School YPLP PGRI 1 Makassar - Amanurhidayani, Amanurhidayani; Kana, Sylvana; Akib, Haedar; Darwis, Muhammad (Universitas Negeri Makassar, 2019)
A conducive school climate and culture is characterized by the creation of a safe, comfortable and orderly learning environment so that learning can take place effectively. This study aims to describe the organizational culture, description of student learning motivation and the influence of organizational culture on learning motivation of class X students in office administration skills competencies in SMKÂ YPLP1 PGRI Makassar., amounting to 66 students. Data collection used in this study were observation, questionnaire and documentation. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results showed that organizational culture belonged to the good category, viewed from seven indicators, namely innovation, stability, orientation to people, orientation to results, calm, attention to details and orientation to collaboration. Student learning motivation is categorized as very good, in terms of five indicators, namely the desire and desire to succeed, the encouragement and need for learning, the hopes and ideals of the future, the existence of interesting activities in learning and the existence of a conducive learning environment. Furthermore, there is a cultural influence on the learning motivation of students in class X competence in office administration skills classified as moderate and accepted.